Biodecolorization of Azo Dye using Trametes sp. UM 12 Isolated from East Kalimantan - Retno Wulandari; Mitha Mitha; Abdul Kahar; Eko Heryadi; Muhammad Fahmi; Rif'an Fathoni; Rosa Assyifa Firyaal; Wahyudi Rangga (Malikussaleh University, Aceh, Indonesia, 2026)
The textile industry releases substantial amounts of azo dyes, including Reactive Black 5 (RB5), which persist in the environment due to their stable chemical structures and toxic properties. White-rot fungi-based biological treatment serves as an environmentally friendly and affordable method for removing dyes from water through the production of ligninolytic enzymes, including laccases. The research assesses Trametes sp. UM 12's decolourisation ability compared to Phanerochaete chrysosporium for RB 5 decolourisation efficiency. The research examined the effects of pH, temperature, agitation speed, and initial RB5 concentration on fungal decolourisation. The optimal removal of Trametes sp. was achieved at pH 5 and 30–35°C with 150 rpm agitation, resulting in more than 95% colour removal within 48–72 hours, and it reached 99.7% decolourization after 96 hours at 100 mg/L RB5. The process removed 98.7% and 96.8% of the dye at 100 mg/L and 250 mg/L after 120 hours, but only 52.1% and 31.8% at 500 mg/L and 1000 mg/L, respectively. The process shows substrate inhibition and enzyme saturation at high pollutant concentrations. The research shows Trametes sp. UM 12 outstanding performance, making it suitable for treating wastewater in tropical environments.